أليس الصبح بقريب (Alaysa al-subh bi-qarib - al-ta'lim al-'Arabi al-Islami dirasah tarikhiyyah wa ara' Islahiyyah) - Ibn Ashur, Muhammad al-Tahir (Dar al-Multaka and Hay'at al-A'mal al-Fikriyyah, 2010)
The book deals with issues of substantive and institutional reform of Islamic education and learning.